2000
DOI: 10.1088/0022-3727/33/7/301
|View full text |Cite
|
Sign up to set email alerts
|

Fibre optic jacket removal by pulsed laser ablation

Abstract: Several applications of optical fibres for sensor and telecommunications require the polymer jacket to be stripped from the fibre, e.g. for the inscription of Bragg gratings. Here, we report an alternative approach to chemical and mechanical fibre jacket stripping based on laser ablation. It is shown that excellent quality removal is possible using the ultraviolet excimer and infra-red CO2 laser, provided the latter is tuned to a suitably strong absorption band in the polymer. Characterization of the ablation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 11 publications
(16 reference statements)
0
13
0
Order By: Relevance
“…However, there are disadvantages of using these techniques, such as structural damages and environmental effects. Laser ablation for removal of material has been found to overcome the limitations of traditional methods . Further, researchers are investigating laser ablation for jacket striping of single‐mode fiber, which has a dual polymer layer system …”
Section: Applications Of Laser Ablation Of Polymersmentioning
confidence: 99%
“…However, there are disadvantages of using these techniques, such as structural damages and environmental effects. Laser ablation for removal of material has been found to overcome the limitations of traditional methods . Further, researchers are investigating laser ablation for jacket striping of single‐mode fiber, which has a dual polymer layer system …”
Section: Applications Of Laser Ablation Of Polymersmentioning
confidence: 99%
“…Other authors have investigated and demonstrated the use of CO 2 lasers to ablate and remove the polymer coating [20]. We are currently in the process of implementing this technique which should eventually allow for a completely operator independent, automated fibre end-face preparation system.…”
Section: Resultsmentioning
confidence: 99%
“…figure 3). Precise cleavage of the fibre is not required at this stage, as this process can be performed further along the production line using laser processing [21].…”
Section: Optimization Of the Automation Parametersmentioning
confidence: 99%